Relationship of surfactant protein-D with random blood glucose and extra pulmonary infections in type-2 diabetes mellitus - Shireen Jawed; Komal Atta; Sadaf Zia; Benash Altaf (Journal of the Pakistan Medical Association, 2020)
Objectives: To compare surfactant protein-D levels in type 2 diabetics and non-diabetics, and to explore its link with random blood glucose and extra-pulmonary infections. Methods: The case-control study was conducted in 2012-13 at the Dow University of Health Sciences, Karachi, and comprised diabetic cases and non-diabetic controls. Extra pulmonary infections, body mass index and random blood glucose levels were noted and serum surfactant protein-D was analysed using enzynme-linked immunosorbent assay. Data was analysed using SPSS 20. Results: Of the 120 subjects, 60(50%) each were cases and controls. Significant negative correlation was found between surfactant protein-D and infections (rs= -0.495, p=0.0001). A negative association between random blood glucose and surfactant protein-D was found, but it was not significant (p=0.15). Relative risk for extra-pulmonary infections in diabetics was 2 times higher than the controls (odds ratio: 2.10, p=0.04). Conclusion: Serum surfactant protein-D was found to have negative association with extra-pulmonary infections. Key Words: Extra-pulmonary infections, Hexokinase method, Random blood glucose, Continuous...